Low‐Dose Coconut Oil Supplementation Induces Hypothalamic Inflammation, Behavioral Dysfunction, and Metabolic Damage in Healthy Mice. Issue 10 (17th April 2021) - Veras, Alana Carolina Costa; Santos, Tamires dos; Martins, Isis de Cássia Alves; de Souza, Camilla Mendes; Amaral, Camila Libardi; Franco, Beatriz da Silva; Holanda, Alessandro Spencer de Souza; Esteves, Andrea Maculano; Milanski, Marciane; Torsoni, Adriana Souza; Ignacio‐Souza, Leticia Martins; Torsoni, Marcio Alberto
Abstract : Scope: Coconut oil (CO) diets remain controversial due to the possible association with metabolic disorder and obesity. This study investigates the metabolic effects of a low amount of CO supplementation. Methods and Results: Swiss male mice are assigned to be supplemented orally during 8 weeks with 300 µL of water for the control group (CV), 100 or 300 µL of CO (CO100 and CO300) and 100 or 300 µL of soybean oil (SO; SO100 and SO300). CO led to anxious behavior, increase in body weight gain, and adiposity. In the hypothalamus, CO and SO increase cytokines expression and pJNK, pNFKB, and TLR4 levels. Nevertheless, the adipose tissue presented increases macrophage infiltration, TNF‐α and IL‐6 after CO and SO consumption. IL‐1B and CCL2 expression, pJNK and pNFKB levels increase only in CO300. In the hepatic tissue, CO increases TNF‐α and chemokines expression. Neuronal cell line (mHypoA‐2/29) exposed to serum from CO and SO mice shows increased NFKB migration to the nucleus, TNF‐α, and NFKBia expression, but are prevented by inhibitor of TLR4 (TAK‐242). Conclusions: These results show that a low‐dose CO changes the behavioral pattern, induces inflammatory pathway activation, TLR4 expression in healthy mice, and stimulates the pro‐inflammatory response through a TLR4‐mediated mechanism. Abstract : The daily consumption of small amounts of coconut oil for 8 weeks by healthy Swiss mice induces weight gain, reduced energy expenditure, and locomotor activity. Furthermore, it triggers anxious behavior and central and systemic inflammation, mediated by the increase of inflammatory agents, such as increased gene expression of cytokines and chemokines and activation of inflammatory signaling pathways. The pro‐inflammatory response occurs through a TLR4‐mediated mechanism.